Control system for personnel, fuel and boilers in the boiler house - Kukartsev, V.V.; Dalisova, N.; Muzyka, P.; Yarkova, S.A.; Degtyareva, K.V. (E3S web of conferences, 2023)
This paper tackles the pressing issue of insufficient automation in the boiler room industry, specifically concerning the crucial tasks of data collection and analysis pertaining to boiler status, fuel levels, and employee activity. Presently, these tasks often demand significant manual efforts, resulting in inefficiencies and potential errors. To address this challenge, the paper proposes the development of an innovative and cutting-edge system that aims to revolutionize the industry’s operations. The proposed system promises to seamlessly integrate and consolidate vital information related to fuel consumption, boiler performance, and employee actions into a unified and compact platform. By doing so, it endeavors to enhance overall efficiency, optimize resource allocation, minimize downtime, and improve decision-making processes. This new system’s successful implementation could potentially lead to greater productivity and safety standards within the boiler room industry, ushering in a new era of streamlined and automated operations.